Factors Associated with Increased Healing Time in Complete Femoral Fractures After Long-Term Bisphosphonate Therapy. (7th December 2016) - Lim, Hae-Seong; Kim, Chong-Kwan; Park, Youn-Soo; Moon, Young-Wan; Lim, Seung-Jae; Kim, Sang-Min
Abstract : Background: The purpose of this study was to analyze factors that affect healing time after operative treatment of complete femoral fractures associated with long-term use of bisphosphonates. In particular, we sought to determine surgically controllable factors related to fracture-healing time. Methods: Ninety-nine consecutive patients (109 fractures) who had been surgically treated for a complete atypical femoral fracture were enrolled. All patients had a documented history of bisphosphonate therapy at the time of presentation, with an average duration of 7.4 ± 3.5 years (range, 3 to 20 years). Baseline demographic data, characteristics of the fracture and surgery, and radiographic findings including femoral neck-shaft angle, coronal and sagittal bowing of the femur, and thickness of the femoral cortex were examined. Univariate and multivariate logistic regression analyses were performed to identify predictive factors associated with delayed union or nonunion. Results: Of the 109 fractures, 76 (69.7%) showed osseous union within 6 months after the index surgery and were assigned to the successful healing group. The remaining 33 fractures (30.3%), which showed delayed union or nonunion, were assigned to the problematic healing group. There were differences in body mass index (BMI), bisphosphonate therapy duration, and the rate of prodromal symptoms between the 2 groups. Supra-isthmic fracture location, femoral bowing of ≥10° in the coronal plane, and a lateral/medial cortical thickness ratio of ≥1.4 were predictive of problematic healing but were uncontrollable factors. Iatrogenic cortical breakage around the fracture site as well as a ratio of ≥0.2 between the remaining gap and the cortical thickness on the anterior and lateral sides of the fracture site were controllable predictive factors associated with problematic healing. Conclusions: Intramedullary nailing without cortical breakage around the fracture site and decreasing the anterior and lateral fracture gaps (avoidance of distraction) as much as possible are recommended to reduce healing time in complete femoral fractures associated with long-term use of bisphosphonates. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.